Tourism value chain for competitive advantage creation in Indonesia tourism - Rahmiati, Filda; Othman, Norfaridatul Akmaliah (Penerbit UTeM Press, 2022)
Companies struggle to develop creative marketing strategies to retain existing consumers and attract new ones in today’s highly competitive market environment. However, from a consumer’s perspective, increased competition means that consumers have more options to choose. Accordingly, sophisticated consumers are selecting better options from various alternatives based on the value obtained from the choices. Therefore, businesses should respond with various strategies to enhance consumer value. The concept of consumer value is becoming increasingly important as a factor in gaining a competitive advantage. This book aims to profile value chain creation and establish a database framework in various industries. This book also wishes to demonstrate the creation of superior consumer value as a key element of business success, leading to a sustainable competitive advantage whereby the value a business creates for its consumer cannot be matched by any competitor offers over time. . It highlighted the importance to understand and fulfilling consumer wants and needs through value chain marketing. Value chain marketing can be achieved by identifying relevant activities of all parties along the chain to deliver valuable products and services to consumers.